2017
DOI: 10.1111/1365-2664.12994
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed burning, atmospheric pollution and grazing effects on peatland vegetation composition

Abstract: Abstract1. Peatlands are valued for ecosystem services including carbon storage, water provision and biodiversity. However, there are concerns about the impacts of land management and pollution on peatland vegetation and function.2. We investigated how prescribed vegetation burning, atmospheric pollution and grazing are related to vegetation communities and cover of four key taxa (Sphagnum spp., Calluna vulgaris, Eriophorum vaginatum and Campylopus introflexus) using two datasets from a total of 2,013 plots ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…Furthermore, contrary to the claims in their paper that suggested that EMBER did not control for site effects, A&H do actually point out that a statistical analysis of the EMBER data included site as a random factor within models when examining the effect of several environmental variables on vegetation (Noble et al, 2018). Curiously, A&H decided for themselves that this "was not associated with the main EMBER project", despite the fact that the funding and acknowledgements of the Noble et al (2018) paper are clearly attributed to the EMBER grant, three of the authors were from the EMBER team, and that the paper investigated the EMBER plots. Importantly, Noble et al (2018 p565) already showed that "the vegetation of the unburned sites shows a clear divide between North and South Pennine sites in the EMBER NMDS ordination in line with the two mire NVC [National Vegetation Classification -(Rodwell, 1991)] types they supported.…”
Section: Results and Discussion 31 Re-examination Of Ashby And Heinemementioning
confidence: 81%
“…Furthermore, contrary to the claims in their paper that suggested that EMBER did not control for site effects, A&H do actually point out that a statistical analysis of the EMBER data included site as a random factor within models when examining the effect of several environmental variables on vegetation (Noble et al, 2018). Curiously, A&H decided for themselves that this "was not associated with the main EMBER project", despite the fact that the funding and acknowledgements of the Noble et al (2018) paper are clearly attributed to the EMBER grant, three of the authors were from the EMBER team, and that the paper investigated the EMBER plots. Importantly, Noble et al (2018 p565) already showed that "the vegetation of the unburned sites shows a clear divide between North and South Pennine sites in the EMBER NMDS ordination in line with the two mire NVC [National Vegetation Classification -(Rodwell, 1991)] types they supported.…”
Section: Results and Discussion 31 Re-examination Of Ashby And Heinemementioning
confidence: 81%
“…Acrocarpous mosses increased over the study period in B1 plots at the Cheviot site, possibly owing to the higher proportion of bare peat at this site after burning. Ceratodon purpureus, an acrocarpous moss common in the Cheviot B1 plots, has previously been observed to colonise bare ground after fire (Duncan and Dalton 1982;Thomas et al 1994), as have other acrocarpous mosses including Campylopus introflexus (Equihua and Usher 1993;Noble et al 2018). It is possible that extensive colonisation by acrocarpous mosses after fire could negatively affect the regeneration of other vegetation owing to a tendency to rapidly carpet bare ground, providing a poor substrate for young plants of other species, and potentially competing for resources (Equihua and Usher 1993).…”
Section: Figmentioning
confidence: 99%
“…However, this trend over time was driven by relatively low cover in a few patches so caution is needed in interpreting this result. Differences in Sphagnum abundance (and vegetation composition more generally) between sites could be the result of variation in current and historic atmospheric pollution (Table 1), which is known to affect several peatland plants including Sphagnum (Noble et al 2018). Other potential causes of differences between the sites include climate (e.g.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of such management is generally to produce a mosaic of small (circa 30 m) fires to improve grazing for sheep and deer and to provide diverse habitat structures that benefit feeding and nesting of red grouse (Lagopus lagopus scotica Latham, 1787) and other birds (Pearce-Higgins and Grant 2006; Robertson et al 2017). In the U.K. there is, however, considerable controversy over the effects of this management practice due to (1) failure to adequately account for interactions between multiple disturbances including drainage, grazing, nutrient deposition, and fire (Davies et al 2016a;Noble et al 2018); (2) lack of recognition of the resilience of keystone peatland species, such as Sphagnum L. spp., to fire Taylor et al 2017); and (3) unquantified trade-offs between multiple ecosystem services such as carbon sequestration in organic and peat soils (Ward et al 2007), regulation of catchment hydrology and water quality (Holden et al 2012;Brown et al 2013), agricultural and game production, and the conservation of unique moorland biodiversity (Thompson et al 1995).…”
Section: Introductionmentioning
confidence: 99%